Γ-limit for two-dimensional charged magnetic zigzag domain walls - Knüpfer, Hans; Shi, Wenhui (Archive for rational mechanics and analysis, 2021)
Charged domain walls are a type of domain wall in thin ferromagnetic films which appear due to global topological constraints. The non-dimensionalized micromagnetic energy for a uniaxial thin ferromagnetic film with in-plane magnetization m ∈ S1 is given by ...
Online veröffentlicht am 4. Februar 2021
Im Titel wird das "Gamma" als griechischer Buchstabe dargestellt
Gesehen am 09.01.2023